The relationship between auditory perception and mental images constructed by the visually impaired (Research, Society and Development, 2020)
Visual impairment comprises the population of people who are distinguished into two groups: the blind, those who cannot perceive any visual stimulus, and people with low vision, characterized by a variety of symptoms, such as tube vision, lack of visual acuity, high sensitivity to light, night blindness and difficulty in distinguishing colors. The objective of this work is to understand the contribution of auditory perception in the mental construction of the visually impaired to the composition of images in their daily lives. The research was carried out in the field, in which the data found to answer the study's problem were analyzed through notes of conversations, reports and a semi-structured questionnaire applied through interviews with the visually impaired of the Association of the Blind of Piauí, located in Teresina / PI. The research participants were 30 visually impaired with total lack of vision, of congenital or acquired etiology, of both sexes, aged between 20 and 60 years old and literate. The research found that the visually impaired experience the world through other sensory channels, but the senses that most help them in this process of assimilation and understanding are the auditory and the tactile, contributing greatly to the construction of mental images.